2022
DOI: 10.1002/fsn3.3113
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study on food safety knowledge and practices among food handlers in tertiary and second circle institutions in Ho municipality, Ghana

Abstract: In recent years, incidences of food poisoning have been reported in some schools across the country. However, little attention has been paid to the hygiene practices of food vendors in the schools. This study, therefore, investigates the food safety knowledge and practices of food vendors catering for tertiary and second cycle students in the Ho municipality. The piloted and validated questionnaire used to sample 608 respondents revealed that the majority of the respondents sampled were female (76.0%), between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…This concurs with an earlier Ethiopian meta-analysis that found that food handlers with good food hygiene knowledge were more likely to apply good FHPs than their ignorant counterparts 8 . Poor FHPs could critically affect the health of food consumers, with severe food poisoning and consequently the spread of FBDs; hence, our finding affirms the recommendation by the WHO 11 of frequent assessment of FHP knowledge to prevent FBDs.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This concurs with an earlier Ethiopian meta-analysis that found that food handlers with good food hygiene knowledge were more likely to apply good FHPs than their ignorant counterparts 8 . Poor FHPs could critically affect the health of food consumers, with severe food poisoning and consequently the spread of FBDs; hence, our finding affirms the recommendation by the WHO 11 of frequent assessment of FHP knowledge to prevent FBDs.…”
Section: Discussionsupporting
confidence: 86%
“…The 33 studies 2 , 4 , 6 , 7 , 11 , 12 , 16 42 included were published between 2009 and 2022 and were cross-sectionally designed with a total of 6095 food handlers. Six major studies were carried out in the Greater Accra 2 , 20 , 27 , 28 , 35 , 38 and Volta 6 , 11 , 23 , 25 , 30 , 32 regions, and five were carried out in the Northern region 12 , 21 , 34 , 40 , 41 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations